Factors Associated with Psychoactive Substance Use among In-School Adolescents in Zaria Local Government Area, Kaduna State, Nigeria: A Cross-Sectional Study - Benjamin Oluwasegun Adesina; Ayodeji Matthew Adebayo; Oluwatomi Funbi Iken (Shiraz University of Medical Sciences, 2020)
Background: The use and abuse of psychoactive substances among adolescents pose serious health problems in society. It is crucial to ascertain the factors predisposing adolescents to this in order to enable action by stakeholders. This study was conducted to determine the prevalence and factors associated with psychoactive substance use among in-school adolescents in Zaria Local Government Area (LGA) of Kaduna State, Nigeria. Methods: A descriptive cross-sectional study was conducted in nine secondary schools selected by balloting with a sample size of 639 students. A semi-structured, self-administered questionnaire was used to obtain information on socio-demographics and lifetime/current use of psychoactive substances. Data were analyzed by descriptive statistics, chi-square test, and logistic regression at P=0.05. Results: The mean age of respondents was 15.98±1.52 years, 51% were male, and 54.6% were aged 14-16 years. The lifetime and current prevalence of psychoactive substances were 69.3% and 46%, respectively. Kolanut was the most widely used substance with a lifetime and current use prevalence rates of 56% and 37.6%, followed by 14.4%, 12.8%, and 11% of respondents with lifetime use of sedatives, alcohol, and tobacco, respectively. Respondents' age (OR 2.493 95% CI=1.670-5.185; P=0.001), mothers' educational level (OR 1.703 95% CI=4.201-5.057; P=0.001), family (OR 3.428 95% CI=9.778-8.856; P=0.023) and friends' (OR 2.252 95% CI=1.315-3.856; P=0.003) use of psychoactive substances were predictors of substance use. Conclusions: The study revealed that both lifetime and current use of psychoactive substances among the adolescents were high, especially among the males. Kolanut was the most used psychoactive substance among in-school adolescents, followed by sedatives and alcohol. Age, mothers' educational level, and parents' occupation were predisposing factors to psychoactive substance use.